TRANSLATION TECHNIQUE OF NOUN PHRASE USED BY THE THIRD SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF TIDAR UNIVERSITY - Regian - (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2020)
Translation is a skill about changing language to deliver message from source language into target one. The translation class at Tidar University starts at 3rd semester and those students are novice translators. Since they are novice translator, majority of them use literal translation technique or word by word translation to translate text. The objectives of the research are: 1) to know what translation techniques are used and 2) to know the most dominant translation technique used by the 3rd semester students of English Department of Tidar University.            The type of this research is qualitative descriptive research. The writer collected the data by using documenting the students midterm test of translating English to Indonesia. The writer identifies translation of noun phrase and analyze on Hartono translation techniques(2017).            The results of the analysis show there are 17 noun phrases from 21 sentences and 41 texts. There are 6 translation techniques that were used by the students to translate noun phrase and those are borrowing that were used 3 times or 7.31%, literal translation that were used 16 times or 39.02%, compensation that were used 2 times or 4.87%, established equivalent that were used 2 times or 4.87%, generalization that were used 6 times 14.63% and reduction consist of 11 times or 26.82%. Related to result above, the most dominant translation technique that used by the students is literal translation consist of 16 times or 39.02%.            The writer suggestions are: 1) It better for English Lecturer to teach the students other translation technique so the students can translate noun phrase better. 2) It would be better for the students to try translating the text first to what their understanding, then learn more about translation techniques to help them translating noun phrase that hard to be translated by using literal translation techniques. 3) The writer hoped that by using this research other researchers can carry out a deeper research about translation technique in noun phrase.